Does Divorce Law Matter? - Marco Mariotti; Paola Manzini; Giulio Fella (Institute for the Study of Labor (IZA), 2002)
In this paper we derive an explicit model of negotiations between spouses when utility is (partially) transferable only in case of separation. We show that inefficient separation may occur in equilibrium even under consensual divorce law. This provides theoretical support for the view that changes in social norms rather than in legislation may be responsible for increasing divorce rates.
Keywords: C78; J12; 330; Bargaining; divorce; non transferability; Eherecht; Familienökonomik; Privater Transfer; Verhandlungstheorie; Theorie; Scheidung